2009
DOI: 10.2214/ajr.09.2949
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Spectrum of Venous Thrombotic Disorders Found on PET/CT

Abstract: The division of thrombotic disorders into metabolically nonactive and active thrombus may be helpful for differential diagnosis of underlying diseases causing thrombus formation. IV contrast media administration during PET/CT makes it possible to visualize the thrombus itself and helps to distinguish between benign and malignant metabolically active thrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…It is important to discriminate a bland thrombus from a tumor thrombus due to different treatment strategies in each. [4] The increased FDG uptake in a tumor thrombus is due to high metabolic neoplastic activity. [5] However, a differentiation between a benign (bland) thrombus from a malignant (tumor) thrombus based on increased FDG uptake often cannot be made since varied FDG uptake has also been observed in inflammatory and infectious processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to discriminate a bland thrombus from a tumor thrombus due to different treatment strategies in each. [4] The increased FDG uptake in a tumor thrombus is due to high metabolic neoplastic activity. [5] However, a differentiation between a benign (bland) thrombus from a malignant (tumor) thrombus based on increased FDG uptake often cannot be made since varied FDG uptake has also been observed in inflammatory and infectious processes.…”
Section: Discussionmentioning
confidence: 99%
“…In a remote thrombus, venous expansion and intra-thrombus neovascularity are features which are suggestive of tumor thrombosis. [4] Few studies have well depicted the role of FDG PET CT in differentiating between a bland and a malignant tumor thrombus. Intense FDG uptake is seen in malignant tumor thrombus in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Incidental findings at FDG PET/CT are common1 given FDG uptake is a marker of glycolysis, and in addition to initiate further investigation, may adversely impact the patient’s prognosis, rendering interpretation and recognition of normal variants and important incidental findings critical 2. Although portal vein thrombosis resulting in 18F-FDG uptake is previously described, these cases are associated with a range of malignancies including lymphoma, pancreatic cancer and HCC coexisting with cirrhosis 38.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, FDG-PET was shown to be one of the most reliable diagnostic modalities and therefore of value in the clinical setting of FUO. FDG-PET correlates well with the metabolic activity of a certain lesion such as inflammation ( 3 , 4 , 5 ). FDG-PET/CT is therefore not only of value in the initial localization of the underlying cause of FUO but might also serve as a surrogate marker for a positive therapy response by showing decreased metabolic (inflammatory) activity.…”
Section: Introductionmentioning
confidence: 95%
“…Miceli et al ( 1 ) reported 9 cases of septic deep venous thrombophlebitis localized in vena cava, innominate, subclavian, and internal jugular veins, showing in one case histopathology of an organizing thrombus with neutrophillic cell infiltrate in the vessel wall as the cause for increased FDG uptake. Sopov et al ( 3 ) have made a distinction between non-metabolically active, so-called “bland” thrombi and metabolically active, FDG-positive thrombi as a result of 1. vascular wall inflammation (phlebitis), 2. systemic inflammatory disorder (vasculitis), 3. infection, 4. catheter-related, or 5. tumor tissue thrombus. Although the diagnosis in our patient was not confirmed by histological examination of the thrombus, it is most likely that in our patient central venous thrombosis and -phlebitis was caused by septicemia after septic toe nail extraction and recurrent thrombophlebitis as a result of previous infusion of intravenous antibiotics.…”
Section: Case Reportmentioning
confidence: 99%